Warm/cool-tone switchable thermochromic material for smart windows by orthogonally integrating properties of pillar[6]arene and ferrocene - Wang, Sai; Xu, Zuqiang; Wang, Tingting; Xiao, Tangxin; Hu, Xiao-Yu; Shen, Ying-Zhong; Wang, Leyong (Nature communications, 2018)
Functional materials play a vital role in the fabrication of smart windows, which can provide a more comfortable indoor environment for humans to enjoy a better lifestyle. Traditional materials for smart windows tend to possess only a single functionality with the purpose of regulating the input of solar energy. However, different color tones also have great influences on human emotions. Herein, a strategy for orthogonal integration of different properties is proposed, namely the thermo-responsiveness of ethylene glycol-modified pillar[6]arene ( EGP6 ) and the redox-induced reversible color switching of ferrocene/ferrocenium groups are orthogonally integrated into one system. This gives rise to a material with cooperative and non-interfering dual functions, featuring both thermochromism and warm/cool tone-switchability. Consequently, the obtained bifunctional material for fabricating smart windows can not only regulate the input of solar energy but also can provide a more comfortable color tone to improve the feelings and emotions of people in indoor environments. Materials for smart windows usually possess single functionality, thus developing materials that regulate solar energy whilst changing color to affect human emotion is desirable. Here the authors combine pillar[6]arenes and ferrocene/ferrocenium groups to produce warm/cool tone-switchable thermochromic materials.